2016
DOI: 10.1515/auom-2016-0033
|View full text |Cite
|
Sign up to set email alerts
|

On the binomial edge ideals of block graphs

Abstract: We find a class of block graphs whose binomial edge ideals have minimal regularity. As a consequence, we characterize the trees whose binomial edge ideals have minimal regularity. Also, we show that the binomial edge ideal of a block graph has the same depth as its initial ideal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…T is a cutset of G if c(T \ {i}) < c(T ) for each i ∈ T , and we denote by C(G) the set of all cutsets for G. In [8] and [15] the authors gave a description of the primary decomposition of J G in terms of prime ideals induced by the set C(G) (see (2)). Thanks to this result the following formula for the Krull dimension is obtained (1) dim S/J G = max T ∈C(G)…”
Section: Introductionmentioning
confidence: 98%
“…T is a cutset of G if c(T \ {i}) < c(T ) for each i ∈ T , and we denote by C(G) the set of all cutsets for G. In [8] and [15] the authors gave a description of the primary decomposition of J G in terms of prime ideals induced by the set C(G) (see (2)). Thanks to this result the following formula for the Krull dimension is obtained (1) dim S/J G = max T ∈C(G)…”
Section: Introductionmentioning
confidence: 98%
“…Now we prove the assertions regarding in < (J G ). If i(G) = 0, then J G is the ideal of 2-minors of the matrix (3). It is known that in < (J G ) has a 2-linear resolution.…”
Section: Observe That a Block Graph G Is Decomposable If And Only If mentioning
confidence: 99%
“…Let J G denote the binomial edge ideal of a graph G. The first result showing that reg(J G ) = reg(in < (J G )) without computing all graded Betti numbers was obtained for PI graphs by Ene and Zarojanu [8]. Later Chaudhry, Dokuyucu and Irfan [3] showed that proj dim(J G ) = proj dim(in < (J G )) for any block graph G, and reg(J G ) = reg(in < (J G )) for a special class of block graphs. Roughly speaking, block graphs are trees whose edges are replaced by cliques.…”
Section: Introductionmentioning
confidence: 99%
“…One can observe that if (G 1 , G 2 ) = (K m , G), where K m is the complete graph on m vertices, J Km,G is the generalized binomial edge ideal associate to G. In [10] and [7], unmixedness and Cohen-Macaulayness of binomial edge ideal of a pair of graphs are characterized in some special cases. The algebraic properties of the class of generalized binomial edge ideals are widely open, although some results are known (see for instance [7,15,8] and the reference therein). An interesting problem is to determine a classification of the Cohen-Macaulay generalized binomial edge ideals.…”
Section: Introductionmentioning
confidence: 99%